(untitled) (Carte Romanze, 2020)
In the literary 20th century Umberto Eco is amongst the most prolific inventors of words, which are almost always playful, especially in his brilliant literary pastiches. In this study, which only examines the two Diari minimi by Eco, some structural and linguistic strategies are described, and the creation and composition of some new words are studied